Breast Cancer With a HER2 IHC2+ and FISH HER2/CEP17 Ratio ≥2.0 and an Average HER2 Gene Copy Number <4.0 per Tumor Cell: HER2 mRNA Overexpression Is a Rare Event - Liu, Yuanyuan; Wu, Shafei; Shi, Xiaohua; Mao, Feng; Zeng, Xuan (Frontiers in Oncology, 2020)
Purpose: For breast cancer, accurately illustrating HER2 characteristics is a critical precondition for evaluating the prognosis and predicting the efficacy of anti-HER2 therapy. Our purpose was to expose HER2 mRNA expression through an in situ hybridization assay (RNAscope), to aid the identification of HER2 status in breast cancers with a previously controversial classification for patients suffering from a HER2 IHC2+ and HER2/CEP17 ≥2.0 and a <4.0 mean HER2 gene copy number/cell (entitled FISH group 2 by update 2018 HER2 testing guideline). Methods: A total of 8,983 cases of breast cancer with a known HER2 status detected by initial IHC, and a necessary reflex FISH assay for those with IHC2+, were retrospectively analyzed. Then, 41 cases of HER2 IHC2+ in the FISH group 2 were collected and a RNAscope was performed. Results: The incidence of breast cancers with IHC2+ and in the FISH group 2 was 0.46% (41/8,983) in our single-institutional study cohort. In most of the cases (27/41, 65.9%), low levels of HER2 mRNA expression (score 1 and 2 by RNAscope) were demonstrated. Only one case (1/41, 2.4%) of high-level HER2 mRNA expression (score 4 by RNAscope), harboring a FISH HER2/CEP17 ratio of 2.06 and an average HER2 copy number of 3.70, was revealed. One case with the highest FISH HER2/CEP17 ratio of 3.90, showed the lowest level of HER2 mRNA expression (score 1 by RNAscope). Two cases with the same highest average HER2 signals/cell (3.95) by FISH possessed score 3 and score 2 with RNAscope, respectively. No cases with a score of 0 by RNAscope occurred in our sample. In the majority of cases (35/41, 85.4%), hypodisomy of chromosome 17 (average CEP17 signals/cell ≤1.75) was observed. There was no significant relationship between the mRNA expression and FISH results (average HER2 signals/cell, average CEP17 copy number, or HER2/CEP17 ratio) and clinicopathological features (ER and PR statuses, Ki 67 index, tumor size and lymphatic metastasi) in our population. Conclusion: HER2 mRNA overexpression was not a feature in our group of patients. Based on our data, breast cancers with HER2 IHC2+ and in FISH group 2 support a categorization of HER2 negative.